Apoptotic effects of lithium chloride on renal cells and potential alteration of renal antigens involved in systemic lupus erythematosus. - Lucas, Kirsten Clare (My University, 2008)
Lithium, a prophylactic drug for the treatment of bipolar disorder, is used with caution due to many toxicity implications. In particular, lithium dosage and renal toxicity has to be constantly monitored in these patients. Contrary to the above, lithium was found to prevent end-stage renal failure in a subset of female mouse models (NZB/W F1) of systemic lupus erythematosus (SLE). The aim of this study was to investigate the direct effects of LiCl on two established porcine renal tubule cell lines, (LLC-PK1 and PK(15)) to ascertain lithium toxicity, mode of cell death and potential alteration of renal antigens that may lead to the preservation of kidneys in lupus patients. Lithium toxicity was determined using standard cell counts and viability studies. The cells were sensitive to lithium at concentrations of 10 mM and above. Light and electron microscopy, DNA fragmentation and TUNEL assays were performed and established the mode of cell death to potentially be apoptotic. The distal renal tubule PK(15) cells were more susceptible to lithium toxicity than the proximal renal tubule LLC-PK1 cells. Proteins involved in apoptotic mechanisms were investigated for their involvement in lithium induced cell death of the renal cells. Immunocytochemistry (Bax, p53, proliferating cell nuclear antigen (PCNA), retinoblastoma protein (Rb)), Western blots (Bax, Bcl-2, p53) and enzyme activity assays (caspase 3, 8, 9) were used as assessment techniques. No significant difference in the expression of Bax, Bcl-2, p53 and PCNA proteins in LLC-PK1 cells treated with concentrations of up to 20 mM LiCl for 24 h were observed. Conversely, a statistical significant upregulation (p<0.05) of the cell cycle protein, Rb, was noted in 5 and 10 mM LiCl treated LLC-PK1 cells. Flow cytometry with propidium iodide stained cells, however, revealed no change in the cell cycle of the LLC-PK1 cells after LiCl treatment for up to 48 h. Caspase enzyme activity, a hallmark of conventional apoptosis, was assessed using specific substrates. No changes were observed in the initiator caspase 8 or 9, nor in the executioner caspase 3 activities of lithium treated LLC-PK1 cells. However, lithium chloride (20 mM) significantly increased Bax expression in PK(15) cells and the Bax:Bcl-2 ratio, an indicator of apoptosis, increased in a LiCl concentration dependant manner (p<0.05). Furthermore, PCNA and Rb proteins were upregulated (p<0.05) at 10-20 mM and 5-10 mM LiCl respectively. Flow cytometry indicated that LiCl increased the G2/M population of PK(15) cells. Although the results implicate apoptosis as a mechanism of PK(15) cell lithium induced cell death, they indicate that the cells are probably undergoing cell death via a caspase independent mechanism. Well characterised SLE patient serum was used in Western blots to establish whether LiCl caused autoantigenic changes in PK(15) or LLC-PK1 cells. Although initial experiments indicated some changes in autoantigens, particularly SSB-La antigens, further experimentation revealed no consistant changes. In addition, phosphorylation and glycosylation studies did not indicate any changes in autoantigenic structure within the cells. To conclude, this study revealed that LiCl was toxic to established porcine renal tubular cells at concentrations (10 mM and above) that are much higher than those used therapeutically. Distal tubular PK(15) cells were more susceptible to lithium than proximal renal LLC-PK1 cells and the toxicity seemed to be via a caspase independent mechanism of apoptosis. The study also revealed that lithium probably does not alter autoantigens to an extent that immunoprecipitation of antibodies can be prevented in SLE patients and thus the preservation of NZB/W F1 female mice by lithium chloride may be due to another mechanism.
Thesis (Ph.D. (Biochemistry)) -- University of Limpopo, 2008
Keywords: Lithium chloride; Antigens; Lupus erythematosus; Systemic lupus erythematosus; Apoptosis; Kidneys -- Calculi; Lithium chloride; Antigens; Lupus erythematosus; Systemic lupus erythematosus; Apoptosis; Kidneys -- Calculi